REGULATION AND IMPLEMENTATION OF HALAL CERTIFICATION IN INDONESIAN FASHION PRODUCTS (An Analytical Study of Law No. 33 of 2014 on Halal Product Assurance) - Nasution, Evriza Noverda (Faculty of Law, Universitas Pekalongan, 2024)
The halal industry is a growing sector globally, but the implementation of halal certification for fashion products lags behind other products. This study focuses on formulating halal certification for fashion in Indonesia, analyzing obstacles and solutions, and reformulating halal criteria to ensure future compliance with Islamic law. The research, which is normative-empirical, uses legislative, analytical, and case study approaches. Findings indicate that the mandatory halal certification in Indonesia, introduced by Law No. 33 of 2014, is being implemented gradually, with food and beverage products by October 18, 2024, and fashion products by October 18, 2026, as per Government Regulation No. 39 of 2021. The certification authority has shifted from LPPOM MUI to the Ministry of Religious Affairs via BPJPH, which certified over 3 million products by 2023. However, the implementation for fashion products is minimal, mainly covering woven fabrics with animal-derived materials as a critical point. Future halal fashion certification can be enhanced by adding criteria to meet Islamic law requirements. Reformulation of the certification can be achieved by amending PP No. 39 of 2021 or issuing a BPJPH decision on halal indicators for fashion. Challenges include the halal supply chain, lack of globally recognized certification, absence of international halal criteria for fashion, and technological advances causing material distortions. Solutions involve a traceability system to maintain supply chain integrity and global cooperation